2002
DOI: 10.1126/science.1075805
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Soil Faunal Community Composition on Model Grassland Ecosystems

Abstract: Human impacts, including global change, may alter the composition of soil faunal communities, but consequences for ecosystem functioning are poorly understood. We constructed model grassland systems in the Ecotron controlled environment facility and manipulated soil community composition through assemblages of different animal body sizes. Plant community composition, microbial and root biomass, decomposition rate, and mycorrhizal colonization were all markedly affected. However, two key ecosystem processes, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
189
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(202 citation statements)
references
References 22 publications
11
189
0
2
Order By: Relevance
“…The microcosms were maintained in the Ecotron for a period of 8.5 months. Bradford et al (2002) found significant increases in decomposition rate in the most complex faunal treatment, but both mycorrhizal colonization and root biomass were less abundant in the macrofauna treatments. Interestingly plant growth was not enhanced in these treatments, despite higher nutrient (N and P) availability.…”
Section: Models Microcosms and Soil Biodiversitymentioning
confidence: 87%
See 2 more Smart Citations
“…The microcosms were maintained in the Ecotron for a period of 8.5 months. Bradford et al (2002) found significant increases in decomposition rate in the most complex faunal treatment, but both mycorrhizal colonization and root biomass were less abundant in the macrofauna treatments. Interestingly plant growth was not enhanced in these treatments, despite higher nutrient (N and P) availability.…”
Section: Models Microcosms and Soil Biodiversitymentioning
confidence: 87%
“…Bradford et al suggested that respiration was most likely buffered by the combined stimulatory effect of both mesofauna and macrofauna on microbes, which served to maintain microbial activity at a level equivalent to that in the microfauna and mesofauna communities. This study has been considered a benchmark in large-scale microcosm studies, but as Bradford et al (2002) note, it is not a substitute of longer-term in situ field studies.…”
Section: Models Microcosms and Soil Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of other fauna, including meso-or microinvertebrates, also will contribute to the grazing effects recorded here (7,33). Indeed, the exclusion of other common macroinvertebrates, such as diplopods, from experimental chambers means that the invertebrate treatments plots are likely to underrepresent the potential for grazers to regulate the fungal community response to global change (34). However, the unique capacity of isopods to sever and ingest thick fungal cords makes this interaction a particularly strong one within forest soil (20).…”
Section: Discussionmentioning
confidence: 99%
“…The role of diversity per se, however, is unclear. In experiments that removed key taxonomic groups, little change in the rates of soil respiration or above-ground productivity were found (Liiri et al 2002), perhaps because the relatively low degree of specialization among detritivores implies considerable redundancy among this functional group (Bradford et al 2002). Others caution that it may take exposure to multiple types of stresses before there is sufficient loss of buffering capacity due to redundancy within functional groups for changes in ecosystem properties to become apparent (Griffiths et al 2000).…”
Section: The Diversity Issuementioning
confidence: 99%